Prıncıpal Leadershıp And Teacher Performance On Student Success - Halim Purnomo; Mahpudin Mahpudin; Cahyo Setiadi Ramadhan; Abdul Karim; Irfan Fauzi Rahmat (Elementary Teacher Education Program, Majalengka University, 2024)
The determinants of student achievement in schools are widely studied, including factors at school. Research on principal leadership, teacher performance, and student success has been carried out by many other researchers with varied results. This study aims to explain these two factors on student achievement based on teacher and student assessments. The research method used is quantitative through survey techniques. Statistical analysis used is non-parametric statistic Mean-Withney test. This research compared perceptions of teachers and students, male and female, from two school institutions. The comparison results show that both teachers and students agree that the principal has an effect on student achievement (U = 364,000; p = 0.229). In addition, teachers and students agreed that teacher support affected student achievement (U = 369,000; p = 0.266). These results indicate that both students and teachers see a relationship between the leadership role of school principals and teacher performance with student success. These findings can contribute to the development of psychology and education.